2023
DOI: 10.1002/advs.202300686
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Efflux Inhibition by Syrosingopine/LOD Co‐Loaded Nanozyme for Synergetic Self‐Replenishing Catalytic Cancer Therapy and Immune Microenvironment Remodeling

Abstract: An effective systemic mechanism regulates tumor development and progression; thus, a rational design in a one‐stone‐two‐birds strategy is meant for cancer treatment. Herein, a hollow Fe3O4 catalytic nanozyme carrier co‐loading lactate oxidase (LOD) and a clinically‐used hypotensor syrosingopine (Syr) are developed and delivered for synergetic cancer treatment by augmented self‐replenishing nanocatalytic reaction, integrated starvation therapy, and reactivating anti‐tumor immune microenvironment. The synergetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…These nanozymes exhibited the ability to convert GSH to GSSG, thereby inducing ferroptosis, and effectively suppressed tumour growth in mice implanted with HepG2 cells. Other nanozymes, such as Fe 3 O 4 , can enhance antigen presentation by dendritic cells; 116 Fe 2 O 3 can modulate the polarization of tumour-associated macrophages; 117 and manganese ion-based nanozymes activate the cGAS-STING pathway to increase tumour-infiltrating CD8 + T cells. 87 Shen et al designed a nano-metal–organic framework (referred to as mFe (SS)/DG) that incorporated glucose oxidase (GOx) and adriamycin.…”
Section: Synergistic Therapies Involving Nanozymes In Cancer Treatmentmentioning
confidence: 99%
“…These nanozymes exhibited the ability to convert GSH to GSSG, thereby inducing ferroptosis, and effectively suppressed tumour growth in mice implanted with HepG2 cells. Other nanozymes, such as Fe 3 O 4 , can enhance antigen presentation by dendritic cells; 116 Fe 2 O 3 can modulate the polarization of tumour-associated macrophages; 117 and manganese ion-based nanozymes activate the cGAS-STING pathway to increase tumour-infiltrating CD8 + T cells. 87 Shen et al designed a nano-metal–organic framework (referred to as mFe (SS)/DG) that incorporated glucose oxidase (GOx) and adriamycin.…”
Section: Synergistic Therapies Involving Nanozymes In Cancer Treatmentmentioning
confidence: 99%
“…All the supposed antitumoral effects are secondary to this inhibition. Several authors also suggest the main effect of syrosingopine is due to intracellular acidification [ 148 150 ]. In another later publication, Benjamin [ 151 ] suggested that metformin potentiates syrosingopine through intracellular acidic stress-mediated effects.…”
Section: Mct Inhibitorsmentioning
confidence: 99%
“…4C ). 76 In the tumor TME, LOX could catalyze lactate to generate H 2 O 2 in situ while Syr-induced MCT4 downregulation could achieve lactate metabolism blockade, leading to continuous H 2 O 2 production and pH reduction for boosting the Fe 3 O 4 -catalyzed Fenton reaction. Owing to the augmented ROS production and the reversion of the lactate-related immunosuppressive TME, this nanoplatform caused severe immunogenic cell death in tumor cells and promoted antitumor immunity.…”
Section: Pathways Controlling Cdtmentioning
confidence: 99%